Decrease in MAP3Ks expression enhances the cell death caused by hyperthermia. (31st December 2022) - Enomoto, Atsushi; Fukasawa, Takemichi; Terunuma, Hiroshi; Nakagawa, Keiichi; Yoshizaki, Ayumi; Sato, Shinichi; Miyagawa, Kiyoshi
Abstract: Purpose: Hyperthermia is a promising anticancer treatment modality. However, the molecular mechanism underlying the thermal sensitivity of tumor cells is largely unknown. The aim of this study was to clarify how biochemical changes triggered by heat stimulate antitumor activity. Methods and materials: The expression levels of various MAPK members in HeLa cells with or without hyperthermia were evaluated by western blotting and RT-PCR. The intracellular Ca 2+ concentration [Ca 2+ ]i was monitored by digital imaging using CaTM-2 AM. An in vitro cleavage assay was used to determine whether calcium-dependent protease calpain cleaves MAPK components. Cell proliferation and clonogenicity were assessed in the absence or presence of siRNAs targeting MAPK members. Results: Hyperthermia decreased the levels of MAP3K TAK1, RAF1 and MEKK2 but not of the downstream MAP2K and MAPK members. The hyperthermia-induced degradation of TAK1 and MEKK2 was rescued by either the proteasome inhibitor MG132 or the calpain inhibitor ALLN; however, RAF1 was not affected by the inhibitors. Heat induced down regulation of RAF1 . Hyperthermia increased [Ca 2+ ]i and calpain I expression. The calcium ionophore A23187 decreased TAK1 and MEKK2 levels. An in vitro cleavage assay demonstrated that TAK1 and MEKK2 are calpain I substrates. Knockdown of TAK1, RAF1 and MEKK2 suppressed cell proliferation and clonogenicity. Conclusions: Hyperthermia decreased the levels of MAP3K TAK1, RAF1 and MEKK2, without reduction of the downstream components in the MAP3K-MAP2K-MAPK cascade, by a calpain-dependent degradation pathway or transcriptional regulation. TAK1, RAF1 and/or MEKK2 play crucial roles in cell proliferation and clonogenicity and are potential molecular targets for hyperthermia.